Structural-Functional Characteristics of Social System and Problems of Management (Methodological Aspects) - Hovhannisyan, Hovhannes (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
Fundamental elements of the social system and their functional features are analyzed in the article from the positions of middle levels theory and methodology of structural functionalism. The article studies structural and functional aspects of institutionalization and institutional crises, demonstrations of evident and not evident functions in the administrative decision-making context. Efficiency and expediency of system approach in cases of problem resolution are substantiated. The article analyzes definite examples of problems of Armenia in 2010-2014 arising during making decisions at various levels of public management and their implementation, methodologically effective ways to overcome these problems.
Keywords: social system, management, social institutions, institutionalization, institutional crisis, structure, explicit and latent functions